Quantitative assessment of symmetry recovery in navigation-assisted surgical reduction of zygomaticomaxillary complex fractures. Issue 2 (February 2019) - Bao, Tingwei; Yu, Di; Luo, Qifeng; Wang, Huiming; Liu, Jianhua; Zhu, Huiyong
Abstract: Purpose: To evaluate the effects of surgical navigation in zygomaticomaxillary complex (ZMC) fracture reduction. ZMC symmetry was assessed quantitatively. Materials and methods: The sample comprised 25 patients who underwent surgical reduction of comminuted ZMC fractures. They were divided into two groups according to the use of surgical navigation. Reduction outcomes were evaluated using three-dimensional computed tomography models. Five pairs of landmarks were identified on all craniofacial models, and asymmetry scores were calculated based on their coordinates. In quantitative analyses, symmetry and orbital volume were compared between groups. Results: All patients recovered uneventfully. Greater symmetry was observed in the navigation group than in the control group for three of the five pairs of landmarks ( p < 0.05). Although postoperative volumes of the injured orbits were similar between the two groups ( p > 0.05), reduced orbital volumes were larger in the navigation group, indicating better restoration of the fractured orbits ( p < 0.05). Conclusions: The use of surgical navigation can increase postoperative symmetry of the bilateral ZMC. The quantitative evaluation of clinical outcomes is precise and highly reliable.